Mechanism and complex roles of HSC70/HSPA8 in viral entry - Qiaoqiao Chen; Yiwen Chen; Chenxuan Bao; Huayuan Xiang; Qing Gao; Lingxiang Mao (Virus Research, 2024)
The process of viruses entering host cells is complex, involving multiple aspects of the molecular organization of the cell membrane, viral proteins, the interaction of receptor molecules, and cellular signaling. Most viruses depend on endocytosis for uptake, when viruses reach the appropriate location, they are released from the vesicles, undergo uncoating, and release their genomes. Heat shock cognate protein 70(HSC70): also known as HSPA8, a protein involved in mediating clathrin-mediated endocytosis (CME), is involved in various viral entry processes. In this mini-review, our goal is to provide a summary of the function of HSC70 in viral entry. Understanding the interaction networks of HSC70 with viral proteins helps to provide new directions for targeted therapeutic strategies against viral infections.